Determination of Physical and Engineering Properties of Hydrogel Granules for Designing the Mechanical Hydrogel Applicator - Patil, D. V.; Mani, Indra; Singh, Anupama; Varghese, Cini (International Journal of Bio-resource and Stress Management, 2023)
Hydrogels are hard, off white amorphous polymers (hydrophilic materials) in physical appearance which have tendency to expand when they come in contact with water. Basically, the use of hydrogel granules is in the arid and semi-arid zone areas which receive less rainfall and having low soil moisture. PUSA Hydrogel can absorb water 350-450 times of its dry weight and gradually releases the same. The physical and engineering properties for three different sizes of hydrogel namely MS18, MS25 and MS36 were determined to design the metering mechanism of a mechanical hydrogel applicator for recommended hydrogel application rate i.e. 3 kg ha-1. The hopper for hydrogel applicator machine was designed based on engineering properties like average angle of repose, coefficient of friction and bulk density of the different sizes of hydrogel granules. The distribution pattern for the recommended granule rate was affected by both size and shape of hydrogel granules. Free flow of granules in the hopper was influenced by angle of repose and coefficient of static friction. As mesh size (MS) of hydrogel granules increased, the roundness and spericity of hydrogel granules also increased. Angle of repose and coefficient of internal frictional on both mild steel and Aluminum surface increased when the mesh size of hydrogel granules was increased from MS18 to MS36.